Về khoảng cách giữa các giá trị của biến ngôn ngữ trong đại số gia tử - Hồ, Nguyễn Cát; Sơn, Trần Thái (Journal of Computer Science and Cybernetics, 2016)
This paper deals with the properties of distances between values of linguistic variables in the Hedge Algebras. The result allows to solve some problems of fuzzy ranking in the case, when the expert’ s opinions are words of a natural languages.